O setor serviços no Brasil - Pereira, Vinicius Rena [UNESP] (2014)
This dissertation investigates the tertiarisation of the Brazilian economy, between 2000 and 2009, from the productive structure. Also evaluates if the increase in the deficit of the balance of services in the recent period (2005-2013) is conjunctural or structural, identifying productive activities responsible for the deterioration and linking to the ability to induce economic growth. The methodology was based on the calculation from the input-output matrix, the multipliers of production and employment; the levels of Hirschman-Rasmussen intersectoral relations and intersectoral connection indices pure in GHS methodology. The paper concludes that the tertiarisation of the Brazilian economy has centralized in activity with low wages, multipliers and rates of intersectoral relationship while the deficit of the balance of services has centralized in activities with exactly opposite characteristics